2022
DOI: 10.1002/agt2.185
|View full text |Cite
|
Sign up to set email alerts
|

Down‐conversion materials for organic solar cells: Progress, challenges, and perspectives

Abstract: Organic solar cells (OSCs) in terms of power conversion efficiency (PCE) and operational lifetime have made remarkable progress during the last decade by improving the active layer materials and introducing new interlayers. The newly developed wide bandgap organic donor and low bandgap acceptor molecules covered the absorption from the visible to the near-infrared region. Whereas the incident high energy region (UV) is not in favor of OSCs. Its absorption causes thermalization losses and photoinduced degradati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 157 publications
(196 reference statements)
1
25
0
Order By: Relevance
“…In another study, the upconversion efficiency of the Yb 2 O 3 polycrystal was also shown to be at least one order higher than the well-known β phase NaYF 4 :Yb 3+ , Er 3+ . Some of the conspicuous applications involve but are not limited to metal codoping for innovative photovoltaics, using different excitation ranges (electronic configuration) to obtain upconversion luminescence and external modifications to obtain up- or downconversion. , …”
Section: Applications and Prospects Of Rare Earth Oxidesmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, the upconversion efficiency of the Yb 2 O 3 polycrystal was also shown to be at least one order higher than the well-known β phase NaYF 4 :Yb 3+ , Er 3+ . Some of the conspicuous applications involve but are not limited to metal codoping for innovative photovoltaics, using different excitation ranges (electronic configuration) to obtain upconversion luminescence and external modifications to obtain up- or downconversion. , …”
Section: Applications and Prospects Of Rare Earth Oxidesmentioning
confidence: 99%
“…15 Some of the conspicuous applications involve but are not limited to metal codoping for innovative photovoltaics, 74 using different excitation ranges (electronic configuration) to obtain upconversion luminescence 75 and external modifications to obtain up-or downconversion. 76,77 Aside from the implementation in conversion, REOs are also being used for surface modification in porous silicon-based solar cells. The degradation of the porous electrode surface due to the environment may create additional trap states in the prohibited bands that limit the wafer efficiency.…”
Section: Applications and Prospects Of Rare Earth Oxidesmentioning
confidence: 99%
“…[ 95 ] However, in practicality, this convention is not followed and the term DC is used for materials with a less‐than‐unity QE. [ 96 ] In this review, the DC term has been used for reported materials. The DC materials can be used to overcome the poor blue response of solar cells.…”
Section: Materials and Their Properties For Solar Cellsmentioning
confidence: 99%
“…The DS and DC materials both involve an optical process of converting high-energy photons to lower-energy ones. Differently, DC converts one high-energy photon into two lower-energy ones, while DS converts one high-energy photon into another photon with lower energy [ 45 ]. For this reason, the DC differs from the DS in regard to their quantum efficiency.…”
Section: Working Principle and Figure-of-merit Of Spectral Conversion...mentioning
confidence: 99%